Provision of Learning Room Facilities for School Age Children to Increase Learning Motivation in Semen Village, Gandusari, Blitar Regency, East Java - Sri Wiwoho Mudjanarko; Muhammad Ikhsan Setiawan; Agus Sukoco; Rofik Jalal Rosyanafi; Rizal Bahaswan; I Putu Artaya; Purwanto Purwanto; Agung Sihono; Alfa Izza Ramadhani; Mesakh Yunanto; Ekki Erlangga (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
Blitar City is part of Blitar Regency in East Java Province. Here, there is also the tomb of Bung Karno, the First President of the Republic of Indonesia and the Proclaimer of Indonesian Independence. The existence of Bung Karno's grave is part of the tourism program in Blitar. In addition, there are other tourist attractions such as in the Semen Village, Gandusari District, Blitar. The existence of this tour will make the community around Semen Village to improve the quality of their education. This educational process requires a good learning space so as to make the educational process more comfortable. This is often done with the learning process carried out at home or around the house due to the covid 19 pandemic era. This service is carried out to improve the educational learning process in Semen Village, Gandusari District, Blitar by providing and increasing the space with a wider capacity. The methodology used is to build a study room using technology as a result of research that has been carried out by the main author. The building is made of Precast Composite Concrete. In addition, the authors conducted a survey on the existence of the construction of learning spaces to the user community. The hope of this service is that the existence of this increased study space will further increase the enthusiasm of the younger generation to learn and be ready to increase the tourism potential in Semen Village, Gandusari District, Blitar